Odpowiedzi

2009-05-10T22:19:38+02:00
A)½y+3=7
½y = 4
y = 8

b)3/5y+2/5=4
3y+2=20
y=6

c)3(y+2)=5
3y+6=5
y=-1/3

d)7(y+3)=5y+2+2y
7y+21=7y+2
21 nie = 2
Równanie sprzeczne

e)y/2+⅓=7/6
3y+2=7
y=3/5

f)(y+3)2-(1-y)=3,5
2y+6-1+y=3,5
3y=-1,5
y =-0,5

g)1/5(y-3)-⅔(y-3/5)+⅓=2/5-⅓(2y-3)
1/5y - 3/5 - 2/3y + 6/15 + 1/3 = 2/5 - 2/3y + 1
1/5y + 4/3 = 2/5 + 1
y = 2 + 5 + 20/3
y =13 + 2/3


h)(2y+4)4=½y+1
8y+16=1/2y+1
7,5y=-15
y=-2

i)(y-2)3+1/15-(2y-5)3=(8-4y)5
3y-6+1/15-6y+15=40-20y
17y + 9 + 1/15 = 40
17y = 30 + 14/15
y = 30 + (14/15) : 17


j)(y-5)2+(2y+3)5+⅓=(y+7)15+y/2
2y-10+10y+15+1/3=15y+105+y/2
12y+5 + 1/3 = 15,5y + 105
3,5y = 105 - (5 + 1/3)
3,5y = 99 + 2/3
y = (99 + 2/3)/3,5